MODEL FOR DISTRIBUTING FUNDS PROGRAM KELUARGA HARAPAN (PKH) IN GAMPONG LAE SIMOLAP, SULTAN DAULAT DISTRICT, SUBULUSSALAM CITY - Yusra Jamali; Cahaya Ulan Sarika; Jasmadi; Vira Asfarina Yusra (Program Studi Ekonomi Syariah, 2024)
The distribution of the Program Keluarga Harapan (PKH) Family Hope Program aims to improve the welfare of the poor through access to education, health and social welfare services. However, in its implementation several obstacles were found, namely inaccurate data collection, recipients who were not on target, and the slow distribution process. This research aims to analyze the effectiveness of the system for determining aid recipients, the mechanism for distributing aid, and the impact of aid on community welfare in Gampong Lae Simolap. This research uses a qualitative approach with descriptive methods. Data collection was carried out through interviews, documentation studies, and observations. The analysis was carried out by referring to indicators of effectiveness, namely target accuracy, timeliness, and changes in the welfare of the beneficiary community. The results of the research show that although the PKH distribution mechanism in Gampong Lae Simolap has followed procedures based on the 2018 Ministry of Social regulations, there are still several weaknesses in data collection and monitoring, such as there are still aid recipients who do not meet the criteria, while families who need it more are not registered. The PKH program has had a positive impact in increasing access to education, health services and economic stability, however the benefits have not been optimal due to the limited amount of assistance and not being well targeted. Therefore, this research recommends increasing the transparency and accuracy of data collection, improving the monitoring system, and adjusting the nominal amount of aid.